PERAN MEDIASI PERTUMBUHAN USAHA KECIL MENENGAH (UKM) PADA HUBUNGAN PENDAPATAN SEKTOR PARIWISATA DENGAN PENDAPATAN ASLI DAERAH (PAD) DI KOTA SURAKATA - TUTI EDIATI (JURNAL WIDYA GANECWARA, 2017)
The purpose of this research were: (1) Examine and measuring the effect of tourism revenue to the original income of Surakarta. (2) Examine and measuring the effect of tourism revenue on the growth of small and medium enterprises (UKM) in the city of Surakarta. (3) Testing and measuring the influence of growth of small and medium enterprises (UKM) to the original revenue of Surakarta city area. (4) To examine the effect of mediation on the growth of small and medium enterprises (UKM) on the effect of tourism revenues on the growth of small and medium enterprises (UKM) in Surakarta city. Â  This research was conducted in Surakarta City. The data used in this study is secondary data that is the original income of Surakarta, revenue of the tourism sector, and the growth of small and medium enterprises. Data collected from 2010 to 2016. The data analysis tool using path regression. Â  The results of this study can be concluded that the income of the tourism sector affect the local revenue; Tourism revenues affect the growth of small and medium enterprises; The growth of small and medium enterprises has an effect on the local revenue. It is also known that the growth of small and medium enterprises fully mediates the relationship between tourism revenues and local revenues.